The CORRELATION BETWEEN EXCLUSIVE BREASTFEEDING WITH CHILDREN GROWTH 1-3 YEARS IN THE REGION OF YOGYAKARTA CITY - Mina Yumei Santi; Heni Puji Wahyuningsih; Vita Wulandari (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Exclusive breastfeeding is a risk factor for children's growth. Coverage of exclusive breastfeeding in Special Region of Yogyakarta Province in 2018 only reached 75.9% with the lowest presentation in Yogyakarta City (67.4%) and 11.5% of children under five in Indonesia experienced growth and development abnormalities. The aim of this research was to determine the correlation of exclusive breastfeeding with the growth of children aged 1-3 years in the Yogyakarta City Region. Research method was by an analytical survey with a retrospective cohort design, sampling with accidental sampling and obtained 140 samples. Primary data collection through a google form questionnaire. Data were analyzed by frequency distribution test for univariate analysis, chi-square test for bivariate analysis, and logistic regression for multivariate. The distribution of respondents was dominated by normal child growth (88.6%), no history of low birth weight (77.9%), male sex (55%), middle-educated mothers (50%), unemployed mothers (53.6%), and family income ≥ UMR Yogyakarta City IDR1,846,400 (72.9%). The result indicated that there was a correlation between exclusive breastfeeding and the growth of children with aged 1-3 years p-value = 0.001 (<0,05). Children who are not exclusively breastfed have probability 7 times of experiencing abnormal growth compared with those who are exclusively breastfed.